PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS WORLDWALL PADA PELAJARAN MATEMATIKA KELAS VI SDN MEGAMENDUNG 03 - Atiyani Atiyani; Hendro Prasetyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning evaluation is an essential action needed to achieve executed activities in order to define the success rate of a program, including educational programs, by obtaining various relevant data comprehensively and continuously regarding the process and learning outcomes that have been acquired from the learning taught by the educators. The problems encountered in the field during the evaluation process are that students are less interested in the evaluations conducted by the teacher because the students feel bored with evaluation activities that are still carried out conventionally. Therefore, the researcher intends to develop a learning evaluation research product using the online web platform Wordwall.The problems investigated in this research are: 1) How is the Development of Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03? 2) What is the Feasibility of Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03? 3) What is the Practicality of Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03? The objectives of this research are: 1) To produce and Develop a Product in the form of Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03. 2) To determine the Feasibility of Developing Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03. 3) To test the Practicality of Developing Wordwall-based Learning Evaluation in the six grade mathematics subject at SDN Megamendung 03. This research uses the Research and Development (R&D) type with the ADDIE model. The trial subjects were determined by the researcher. This research was conducted at SDN Megamendung 03. The data collection instruments used are interviews, observation, questionnaires, and documentation. The results of this study are: 1) The product produced is that students, who were initially bored and weary, become enthusiastic and happy. As for the teacher, who initially required extra energy and time, it becomes more practical to assess students' learning outcomes because the results are automatically recorded on Wordwall. 2) The overall average result from the evaluation experts was 97%, indicating that the Wordwall evaluation is very feasible to be tested on students, and the distribution of student response questionnaires yielded 89%, indicating that the Wordwall learning evaluation is very suitable for use. 3) The average result of the small-scale student response questionnaire obtained 88% with a very practical category, and the large-scale obtained a percentage of 86% with a very practical category, and the teacher response questionnaire obtained a percentage score of 95% with a Very Practical category. Thus, it can be concluded that this Wordwall-based learning evaluation is feasible to be implemented.